Visegrad Countries and Africa : Security, Resilience, and Cultural Diplomacy in a Changing World - Lucini, Barbara (Journal of Central and Eastern European African Studies, 2024)
The scenario of great international uncertainty and insecurity reconfigures a new and necessary focus on the dynamics between the Visegrad countries and Africa. Through an evolutionary historical perspective and a focus on the complex and delicate contemporary situation, this contribution aims to explore and deepen the type of relations that have been established over the years between the Visegrad countries and Africa. Specifically, the paper considers the policies developed by Visegrad countries with particular attention to three issues: security, resilience, cultural diplomacy, and cooperation. In accordance with these issues, security is a common ground for both Visegrad countries and Africa as the latter geopolitical reality is in different ways affected by political and economic instability that could be adapted through actions of social resilience and support to the communities involved. The aim of this paper is therefore to understand how the issue of resilience is and has been addressed in the relationship between the Visegrad countries and Africa. In this complex framework influenced by the major events of the Covid-19 pandemic and the conflict between Ukraine and Russia, the instruments of cooperation and cultural diplomacy will be considered to better understand the relationship between the Visegrad countries and Africa.